Soil Selenium (Se) Biofortification Changes the Physiological, Biochemical and Epigenetic Responses to Water Stress in Zea mays L. by Inducing a Higher Drought Tolerance - Bocchini, Marika; D’Amato, Roberto; Ciancaleoni, Simona; Fontanella, Maria C.; Palmerini, Carlo A.; Beone, Gian M.; Onofri, Andrea; Negri, Valeria; Marconi, Gianpiero; Albertini, Emidio; Businelli, Daniela (Frontiers in Plant Science, 2018)
Maize (Zea mays L.) requires water and minerals to grow and to develop its organs. Its production and distribution is highly rainfall-dependent and yet current global climatic changes reveal irregular rainfall patterns that result in stress conditions with loss of yield and productivity around the world. It is well known that low water availability leads the plant to adopt a number of metabolic alterations to overcome stress or reduce its effects. To this end, selenium (Se), a trace element, can help limit water damage caused by the overproduction of reactive oxygen species (ROS). Here we report the effects of exogenous Se supply on physiological and biochemical processes that may influence yield and quality of maize under drought stress conditions. Plants were grown in soil fertilized by adding 150 mg of Se (sodium selenite). We verified the effects of drought stress and Se treatment. The suggested Se-biofortification treatment proved its effectiveness in increasing Se concentrations in maize roots and aerial parts. The increase in proline, K concentrations and nitrogen metabolism in aerial parts of plants grown in Se-rich substrates, seems to prove that Se-biofortification increased plant resistance to water shortage conditions. Moreover, the increase of SeMeSeCys and SeCys2 forms in roots and aerial parts of Se-treated plants suggest resistance strategies to Se similar to those existing in Se-hyperaccumulator species. In addition, epigenetic changes in DNA methylation due to water stress and Se treatment were also investigated using Methylation Sensitive Amplified Polymorphism (MSAP). Results suggest Se to be an activator of particular classes of genes that are involved in tolerance to abiotic stresses. In particular, PSY (Phytoene Synthase) gene, essential for maintaining leaf carotenoid contents, SDH (Sorbitol DeHydrogenase), whose activity regulates the level of important osmolytes during drought stress and ADH (Alcohol DeHydrogenase), whose activity plays a central role in biochemical adaptation to environmental stress. In conclusion, Se-biofortification could help maize plants to cope with drought stress conditions, by inducing a higher drought tolerance.